Anti-biofilm activity of dodecyltrimethylammonium chloride microcapsules against Salmonella enterica serovar Enteritidis and Staphylococcus aureus. Issue 1 (11th January 2021) - Khelissa, Simon; Gharsallaoui, Adem; Wang, Jian; Dumas, Emilie; Barras, Alexandre; Jama, Charafeddine; Jbilou, Fouzia; Loukili, Noureddine; Chihib, Nour-Eddine
Abstract: Dodecyltrimethylammonium chloride (DTAC) was trapped into maltodextrins/pectin spray dried microcapsules to improve its activity against Salmonella enteritidis and Staphylococcus aureus biofilms. Two different microcapsules were prepared: uncomplexed DTAC-microcapsules (UDM), containing DTAC and maltodextrins; and complexed DTAC-microcapsules (CDM) containing DTAC complexed with pectin and maltodextrins. The minimum inhibitory concentrations (MIC) of both free and microencapsulated DTAC were investigated against S. Enteritidis and S. aureus . The MICs of DTAC were significantly lower when encapsulated. CDM treatment resulted in a 2 and 3.2 log reduction in S. aureus and S. Enteritidis biofilm culturable biomass, respectively. Microencapsulation reduced the cytotoxicity of DTAC by up to 32-fold. Free DTAC and CDM targeted the cell membrane resulting in the leakage of the intracellular molecules and subsequent cell death. The development of DTAC microcapsules reduced the amount of DTAC required to maintain the high standards of cleanliness and hygiene required in the food processing industries.